FINANCIAL SOVEREIGNTY OF THE JUDICIAL SYSTEM OF UKRAINE UNDER MARTIAL LAW (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The judicial system of Ukraine under martial law is grappling with severe challenges due to underfunding and an unstable revenue structure. Analysis from 2022-2024 reveals alarming funding levels: only 80.9%, 59.6%, and 60.5% of the required amounts, respectively. In 2023, actual court fee revenues were only 61% of what was planned, creating risks for financial stability. Moreover, 88% of expenditures are allocated to salaries, leaving just around 10% for justice administration and system development. These issues are exacerbated by martial law, threatening judicial independence and citizens’ access to justice.The purpose of the article is to develop a methodology for forming adaptive mechanisms for financing the judiciary of Ukraine in conditions of martial law, aimed at ensuring its financial sovereignty.Methods. The research examines judicial financing within public administration using various scientific approaches. A systemic approach identifies key issues and offers solutions for judicial funding. Structural-functional analysis evaluates budget formation and distribution, revealing deficiencies and advocating for the establishment of a Budget Commission in the High Council of Justice. An axiological perspective emphasizes the significance of judicial financial sovereignty for maintaining the rule of law and human rights. The logical method organizes the research and supports conclusions. Overall, general scientific methods like analysis, synthesis, and abstraction enable a thorough study of adaptive financing mechanisms for Ukraine’s judiciary.Results. The study proposes a three-level financial support system for the judiciary: basic guaranteed funding of at least 0.5% of GDP, program-targeted funding, and a reserve fund. This system balances stable base funding with flexibility for crises, clearly differentiating funding sources to reduce underfunding risks. It establishes objective criteria for assessing judicial financial needs, considering quantitative, infrastructure, staffing, and security indicators. Coefficients for case complexity and local specifics enhance the system's adaptability. Additionally, an institutional mechanism is proposed, strengthening the High Council of Justice's role through a new Budget Commission responsible for assessing needs, budget requests, and public reporting on budget execution.Conclusions. The methodological approaches developed for the formation of adaptive financing mechanisms for the judiciary are aimed at creating a sustainable, predictable, and flexible system of financial support capable of ensuring the independence and effectiveness of the judicial system even in emergency situations. The implementation of these approaches requires a comprehensive update of the legal framework, institutional mechanisms, and management practices in the field of judicial financing.
Keywords: judiciary, financial sovereignty, adaptive mechanisms, martial law, budgeting, reserve fund, judicial reform.